On increasing stability in an inverse source problem with local boundary data at many wave numbers. Issue 10 (3rd July 2022) - Isakov, Victor
ABSTRACT: To derive the increasing stability of the source term in the Helmholtz equation from local boundary data, we utilize sharp bounds of the analytic continuation for higher wave numbers, the Huygens' principle, and bounds in the lateral Cauchy problem for the wave equation.